The Philosophy of Accounting Conservatism: Pillars of Transparency and Corporate Responsibility - Retstianingtyas, Myta; Sabaruddin, La Ode; Primasatya, Rieswandha Dio (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
This study investigates the role of accounting conservatism as both a technical tool and a moral framework in enhancing corporate transparency, stakeholder trust, and financial stability. It examines how the integration of moral values, such as prudence, transparency, and responsibility, reinforces accountability in financial reporting. This study employs a qualitative descriptive approach, analysing relevant literature and two illustrative cases—Enron and Lehman Brothers—to highlight the consequences of inadequately applying accounting conservatism and its moral dimensions. The study reveals that accounting conservatism, when applied ethically and strategically, mitigates risk, enhances transparency, and supports sustainable decision- making. However, excessive conservatism or manipulative practices, such as big bath accounting, can distort financial realities and undermine public trust. By integrating axiology and functionalism, this study offers a novel philosophical perspective on accounting conservatism as both a moral and technical foundation for building a transparent and sustainable financial system, contributing to the discourse on ethical corporate governance.